2021
DOI: 10.1017/s0029665121002408
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the awareness and compliance of new food-based dietary guidelines for young children in Ireland

Abstract: The Food Safety Authority of Ireland recently published food-based dietary guidelines for 1-5-year-old children, highlighting that this age group were at risk of inadequate intakes of iron, vitamin D, EPA and DHA (1) . This formed the basis for new Department of Health, healthy eating guidelines for kids (2) .The aim of this study was to investigate awareness of the new guidelines (1)(2) among parents of children aged 1-3 years, and compliance to certain recommendations contributing to intakes of the at-risk n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The FSAI created new recommendations to help improve the poor intakes of said nutrients, including consuming iron fortified breakfast cereals 5 times per week, red meat 3 times per week, fish once per week, and including a daily vitamin D supplement. Previously, it was found that 61% of parents were unaware of the new guidelines, with 33% aware of the new vitamin D recommendation (2) . A large proportion (73%) of preschool children did not meet the red meat recommendation and 35% did not meet the recommendation for fish (2) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The FSAI created new recommendations to help improve the poor intakes of said nutrients, including consuming iron fortified breakfast cereals 5 times per week, red meat 3 times per week, fish once per week, and including a daily vitamin D supplement. Previously, it was found that 61% of parents were unaware of the new guidelines, with 33% aware of the new vitamin D recommendation (2) . A large proportion (73%) of preschool children did not meet the red meat recommendation and 35% did not meet the recommendation for fish (2) .…”
mentioning
confidence: 99%
“…Previously, it was found that 61% of parents were unaware of the new guidelines, with 33% aware of the new vitamin D recommendation (2) . A large proportion (73%) of preschool children did not meet the red meat recommendation and 35% did not meet the recommendation for fish (2) . However, nearly all parents (91%) believed that their toddlers had healthy diets.This study was limited as most parents (79%) reported to have achieved 3 rd level education, thus not representative of the wider population (2).…”
mentioning
confidence: 99%